A Systematic approach for designing a multi-function sit-to-stand mobility assistive device based on performance optimization. (17th January 2019) - Asker, Ahmed; Assal, Samy F. M.
ABSTRACT: Recently, the potential of assistive robots to enhance independence and quality of life for elderly and disabled has been given much attention. Designing a multi-function sit-to-stand assistive device is a challenging task due to the high payload and large workspace requirements. In this paper, a parallel manipulator-based assistive device is proposed to assist in various lower limb activities. The device is constructed based on a non-conventional structure of a 3-R P _ R parallel manipulator, that provides partial kinematic decoupling between position and orientation and suitable singularity-free workspace as well as high rigidity and payload capability. Furthermore, dimensional synthesis based on maximizing the workspace index as well as the global force transmission and stiffness indices, is performed to optimize the device dimensions. A prototype of the device is manufactured based on the optimized dimensions. The ability to assist subjects with different stature heights to stand up in a natural manner is asserted by experiments conducted using the prototype. GRAPHICAL ABSTRACT: